Laminar convective heat transfer in helical tube with twisted tape insert - Kurnia, J.C. (Elsevier Ltd, 2020)
Tape insert has been commonly adopted as heat transfer enhancement method in a thermal system. Most studies dealing with tape insert have been focused on straight tube. Helical coil tube, on the other hand, has been proven to have higher heat transfer than straight tube. It is of interest to combine both enhancement methods and obtain the optimum heat transfer enhancement. The main objective of this study is, therefore, to numerically investigate flow behaviour and the corresponding heat transfer in helical tube with twisted tape insert subjected to constant wall temperature. A three-dimensional computational model is developed based on conservation equations of mass, momentum, and energy, and is validated against the established empirical correlations. Good agreement is achieved between the numerical prediction and the empirical correlation calculation within the considered range of Reynolds (Re=100â2000) and Dean Numbers (De=25â1200). The effects of twist ratio, inlet Reynolds number and wall temperature are evaluated and discussed in the light of numerical result. It is found that adding twisted tape insert in helical heat exchanger can enhance heat transfer performance by up to four times as compared to conventional straight tube heat exchanger, at a cost of higher frictional pressure drop. Lower twisting ratio gives rise to a higher heat transfer enhancement as it promotes higher secondary flow. At low Pr (air), heat transfer enhancement ratio increases as Re is increased; however, at high Pr (water), heat transfer enhancement ratio is higher at Re 500â1000. Finally, Nu and f correlations are developed to predict heat transfer and pressure drop for practical applications. Â© 2020